Financial Statement Fraud Analysis: Financial Stability, External Pressure and Auditing Quality - Honesty, Helga Nuri; Fiola Finomia Honesty; Mia Angelina Setiawan (Universitas Airlangga, 2024)
Fraudulent on financial statements is increasing nowadays. The impact is not only felt by investors but also affects global economic stability. This research aims to collect empirical data to determine whether financial stability, external pressure, and audit quality partially and simultaneously influence financial statement fraud. The research objects are companies from the property and real estate sector listed on the Indonesia Stock Exchange, in 2020 - 2022. Multiple regression analysis was used to test the hypothesis on this research's panel data. The results of data processing indicate that external pressure has a positive effect on financial report fraud, while audit quality and financial stability do not influence financial report fraud.